Visualization of two-phase flow of R410A in horizontal smooth and axial micro-finned tubes. (August 2019) - Yang, Cheng-Min; Hrnjak, Pega
Highlights: 3D printed clear axial micro-finned and smooth tubes are used for visualization. Axial micro-fins do not provide additional force to pull up the liquid inside the tube. Liquid-vapor interface in the micro-finned tube is lower and wavier than the smooth. Part of the liquid is trapped in the micro grooves when the vapor quality is low. Abstract: This paper presents a novel visualization approach to understand the effect of axial micro-fins on two-phase flow behavior inside horizontal round tubes. In order to reflect the real inner geometry in the commercial metal tubes (smooth and micro-finned tubes), clear resin tubes were made by an SLA 3D printer to reproduce the geometry. The 3D printed tube for visualization was installed right after the heat transfer test section. In the heat transfer test section, R410A flow boiling experiments were conducted at 10 °C saturation temperature with heat flux of 15 kW/m 2 . The results indicated the axial micro-fins do not provide additional force to lift up the liquid in the round tube and the annular flow pattern does not occur earlier (at lower vapor quality or mass flux conditions) than the smooth tube. For low mass flux and vapor quality, the liquid-phase refrigerant is easily trapped in the grooves at the top or side of the axial micro-finned tube. The main liquid level in the axial micro-finned tube is, therefore, lower than that in the smooth tube under the same conditions. This liquid level change is quantified by tracing the liquid-vapor interfaces in the captured videos with change point analysis.